Mitigating salt accumulation in recycled brewery effluent through the integration of water treatment, agriculture and aquaculture - Mabasa, Nyiko Charity (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
Water scarcity in South Africa, and globally, presents challenges for industries. It is imperative to develop responsible water use, such as recycling and reusing wastewater from food processing industries such as breweries. The Ibhayi Brewery (SAB Ltd) employs a combination of sustainable treatment processes that include anaerobic digestion (AD), primary facultative ponds (PFP), high rate algal ponds (HRAP) and constructed wetlands (CW) to treat brewery effluent on an experimental scale. The constituent concentrations of these experimentally treated effluents are within the ranges prescribed by local regulations to allow for potential downstream use in agriculture and aquaculture. However, the sodium content in this treated effluent, which originates from upstream cleaning agents and pH control at the onsite effluent treatment facility, is a constraint to the downstream use of brewery effluent. This study addresses the salt problem, by investigating the potential of either reducing/eliminating salt addition at source, or developing alternative techniques for downstream agriculture to mitigate the effects of salt accumulation caused by irrigation with brewery effluent. Four salt-tolerant test crops; Swiss chard (Beta vulgaris), saltbush (Atriplex nummularia), Salicornia meyeriana and sorghum (Sorghum bicolor), grew efficiently in brewery effluent irrigated soils but did not stop sodium accumulation in the growth medium. Swiss chard had the best growth with a wet biomass accumulation of 8,173 g m-2, due to the plant's ability to tolerate saline conditions and continuous cropping. Crop rotation, to limit effects of nutrient depletion in soil, had no significant effect on plant growth suggesting soils were adequately able to provide micro-nutrients in the short-term. Prolonged irrigation with brewery effluent can lead to sodium accumulation in the soil, which was successfully controlled through the addition of soil amendments (gypsum and Trichoderma cultures). These reduced soil sodium from a potentially limiting level of 1,398 mg L-1 to the acceptable levels of 240 mg L-1 and 353 mg L-1 respectively, mainly through leaching. However only Trichoderma improved Swiss chard production to 11,238 g m-2. While crop rotation in this work did not contribute to mitigating the problem of salt accumulation, soil amended with Trichoderma appears to be a potential solution when brewery effluent is reused in agriculture. In an alternative to soil cultivation, CWs were trialled with no significant differences in the sodium concentration of brewery effluent treated along a 15 m lateral flow CW, which could be attributed to evapotranspiration. This was notably accompanied by a desirable 95.21% decrease in ammonia from inlet to outlet resulting in significant improvement in water quality for reuse in aquaculture where ammonia levels are important limiting constraints. While CWs remain a suitable brewery effluent treatment solution, this technology requires additional modelling and optimisation in order to mitigate the problem of salt accumulation in the reuse of treated brewery effluent in agriculture and aquaculture. This research demonstrates the baseline information for such modelling and optimisation. African catfish (Clarias gariepinus) grew in CW treated brewery effluent; however, this growth was moderate at 0.92% bw day-1, whereas Mozambique tilapia (Oreochromis mossambicus) were shown to be unsuited to growth in this system and lost weight with an average specific growth rate (SGR) of -0.98% bw day-1; and both fish species presenting with health related concerns. Hardy fish species such as African catfish can be cultured in brewery effluent, but with risk involved. This was a preliminary study to develop parameters for future dimensional analysis modelling to allow optimisation of the CW, based on nutrient removal rates obtained which will allow for improved downstream aquaculture by reducing or eliminating risks presented in this study. This work has also contributed to a foundation for the development of guidelines that use a risk-based approach for water use in aquaculture. Alternatives to the current in place cleaning agents were considered to mitigate the effects of salt accumulation. Sodium is introduced into the effluent via the use of sodium hydroxide and sodium chlorite for cleaning and disinfection in the brewery, as well as through effluent pH adjustment in the AD plant. The widespread use of outdated legacy cleaning systems and pH adjustment regimes is entrenched in the brewery standard operating procedures (SOP). A cost-benefit analysis (CBA) demonstrated that a change of cleaning and disinfecting regimes to hydrogen peroxide in the brewery, and magnesium hydroxide pH adjustment in the effluent treatment plant addresses the sodium issue upstream in the brewery practically eliminating sodium from the effluent. In addition, a life cycle analysis (LCA) was carried out to assess the environmental impacts associated with the alternative cleaning and pH adjustment scenarios. The LCA showed that electricity consumption during use phase of the chemicals for respective purposes, as well as their production activities were major contributors to the significant environmental impact categories that were assessed. The cleaning scenario employing the use of hydrogen peroxide for both cleaning and disinfection was found to be the most environmentally sustainable. This was attributed to the reduced number of chemicals used compared to the other cleaning scenarios. Dolomitic lime was the pH adjustment alternative with the lowest average environmental impact; but, however, had a higher impact on freshwater eutrophication which is of major concern if the effluent will be reused for irrigation. Magnesium hydroxide was therefore considered to be the better option as a sodium hydroxide alternative for pH adjustment. This mitigates salt accumulation, making treated brewery effluent suitable for reuse in high value downstream agriculture and aquaculture, while employing more environmentally sustainable technologies. Notably, this converts brewery effluent from a financial liability to Ibhayi Brewery, into a product containing water and nutrients that generate income, improve food security, and can create employment in downstream agriculture and aquaculture in a sustainable manner.
Keywords: Brewery waste -- South Africa -- Eastern Cape; Recycling (Waste, etc.) -- South Africa -- Eastern Cape; Water reuse -- South Africa -- Eastern Cape; Irrigation -- South Africa -- Eastern Cape; Sewage Purification Anaerobic treatment; Constructed wetlands; Aquaculture